Using Hidden Markov Model to Recognize Vietnamese Voice - Trần Thu Hà; Trần Tiến Đức (Journal of Technical Education Science, 2012)
The system consists of an encoder transferring the vietnamese voice into commands and execution unit - mobile robot. The encoder is designed by a Vietnamese recognition software using phoneme model Hidden Markov Model ( HMM) and algorithms of Vertebi for recognizing the words or sentence of control command. Optimization and selection of the command words with minimum recognition error, control voice can be male or female. Object as mobile robot controller is designed on the basis of IC STM32F103RCT6.